AKSELERASI DAN PENGEMBANGAN PERBANKAN SYARIAH SEBAGAI LEMBAGA PERBANKAN INDONESIA - Natsir, Muh; Ah, Luk Luk (Universitas Muhammadiyah Magelang, 2006)
The success of syariah banking in the future depend on syariah banking effectivity of risk manage. As conventional banks beside that syariah banking also will other risk. For the example credit, marker risk, liquidity and operation and than prestice risk. Syariah system is hoped can give contribution mean for of people. Syariah system also is hoped can lessen economics risk until lessen probability happen economics crisis. Now, development of the syariah banking the good enough. As alternative finance system, syariah banking have the big source when give profit to society. As we have knoen, risk from profit sharing in the syariah banks less. Indonesian syariah banking is not just another banking maneuver form Bank Indonesian (BI) to grasp more customers than before. Bank Indonesia has an obligation to develop syariah banks which its implementation to prepare strategy, arrange banking, arrange banking determine based on syariah principle. Syariah bank behave for all people. Syariah with Islam regulation or doctrin. Whoever can abuse syariah bank’s finance.